Republic of Kazakhstan : Technical Assistance Report-Scanner Data for CPI Mission. (IMF Staff Country Reports; Country Report ;, 2022)
The purpose of the mission was to assist the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan (BNS) with continuing its modernization of the Consumer Price Index (CPI). This was the first technical assistance (TA) mission to Kazakhstan on scanner data (SD). The mission was delivered remotely.